High flux polyaniline-coated ceramic membrane for effective separation of emulsified oil-in-water. Issue 17 (1st September 2022) - Salhi, Billel; Baig, Nadeem; Abdulazeez, Ismail; Al-Ahmed, Amir; Aljundi, Isam H.
Abstract: Oil separation from oily wastewater is critical for environmental sustainability. In the present study, we report for the first time the facile fabrication of high flux polyaniline-modified ceramic membrane to effectively separate emulsified oil. Aniline was rapidly polymerized in a single step on alumina ceramic support using different monomer concentrations. It was revealed that the alumina membrane modified with 1.0 M aniline monomer is suitable for separating oil/water emulsions with an exceptionally high permeance of 3451 L m −2 .h −1 (L.M.H.) and high separating efficiency. The polyaniline-coated alumina membranes appeared superhydrophilic/superoleophobic w ith negligible fouling behavior. The modified membranes demonstrate a steady oil rejection flux after several cycles with excellent oil-rejection of 97%. The high flux, low operating pressure, and antifouling behavior revealed that these modified membranes are excellent candidates for emulsified-oil separation. Graphical abstract: Image 1